Sustaining library automation in Nigerian academic libraries: the KOHA advantage - Oladokun, Taofeek; Kolawole, Lucia, Folasade (My University, 2018)
This study examined the sustainability of Library Open Source Software (with particular reference to KOHA) in Nigerian academic and research Libraries. Descriptive survey design was adopted with a total number of thirty five (35) libraries which were selected purposefully all over the six (6) geopolitical zones of Nigeria (twenty universities, both privates and publics, ten Polytechnics, and five colleges of education). Structure Questionnaire was used to generate data and this was analyzed using simple frequency and percentage. It was revealed that koha is gaining ground in Nigeria because of its reliability and community involvement. It also revealed that lack of institutional support; inadequate information and negative attitudes of librarians were some of the challenges facing adoption and utilization of koha in Nigeria. The study however made some recommendation.
Supplemental Materials: https://osf.io/8yubv/
Keywords: sustainability; library automation; libraries; koha